THE FRICTION OF ASSITULUNGENG’S TRADITION IN THE FARMER SOCIETY AT THE VILLAGE OF TONRONG LEMPONG DISTRICT OF BOLA WAJO REGENCY - Chairy, Ummul; Dahlan, M.; Santalia, Indo (International Journal of Islamic Studies, 2022)
This research aims to describe the friction of tradition of Assitulungeng in the farmer community in the village of Tonrong Lempong, Sub-district of Bola, District of Wajo. The specification of this research is descriptive, more related to a Qualitative Approach, it is meant to understand the phenomenon or an event behalf of the tradition conducted. In this research, the data analized by using the model that consists of three steps, namely: the step of reduction data, the data identification, investigation of the data validity. Its results that the social friction is not only bordered to a modern community category or a dynamic people, but the friction also conducted to a traditional people. The friction is not only about related to the social system friction, but concerning with the governmental system, education system, statue friction in alive of people, the emergence of new social group in a community et cetera.